2022
DOI: 10.3389/ti.2022.10490
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas Transplantation in Black, Asian and Minority Ethnic Patients-Single Centre Experience in the UK

Abstract: Ethnic disparities in the outcomes after simultaneous pancreas kidney (SPK) transplantation still exist. The influence of ethnicity on the outcomes of pancreas transplantation in the UK has not been reported and hence we aimed to investigate our cohort. A retrospective analysis of all pancreas transplant recipients (n = 171; Caucasians = 118/Black Asian Ethnic Minorities, BAME = 53) from 2006 to 2020 was done. The median follow-up was 80 months. Patient & pancreas graft survival, rejection rate, steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…There was no significant difference in the rates of clinical rejection within the first 2 years for the pancreas or kidneys between Hispanics and whites. These rates were lower than the previously reported rate of approximately 20% for pancreas rejection within the first year in a similar immunosuppression regimen study conducted in Britain that used alemtuzumab induction and steroid‐free maintenance with tacrolimus and mycophenolate mofetil 38 . Our lower rates of clinical rejection may be attributed to the early detection and treatment of subclinical rejection 22 …”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…There was no significant difference in the rates of clinical rejection within the first 2 years for the pancreas or kidneys between Hispanics and whites. These rates were lower than the previously reported rate of approximately 20% for pancreas rejection within the first year in a similar immunosuppression regimen study conducted in Britain that used alemtuzumab induction and steroid‐free maintenance with tacrolimus and mycophenolate mofetil 38 . Our lower rates of clinical rejection may be attributed to the early detection and treatment of subclinical rejection 22 …”
Section: Discussioncontrasting
confidence: 61%
“…These rates were lower than the previously reported rate of approximately 20% for pancreas rejection within the first year in a similar immunosuppression regimen study conducted in Britain that used alemtuzumab induction and steroid-free maintenance with tacrolimus and mycophenolate mofetil. 38 Our lower rates of clinical rejection may be attributed to the early detection and treatment of subclinical rejection. 22 The rates of BKV viremia were similar for Hispanics and whites, including any instance of BKV viremia.…”
Section: Discussionmentioning
confidence: 98%
“…3 But the review article also stressed how donation after cardiac death (DCD) has increased the donor pool for pancreatic transplants. 43 For patients undergoing renal transplants, this year's review focused on preoperative cardiac risk stratification and intraoperative resuscitation, including an RCT, in which Collins et al showed a significantly decreased incidence of delayed graft function with balanced crystalloids compared to normal saline, 44,45 Furthermore, the authors elaborated on regional anesthetic techniques supplementing pain control following renal transplantation. While a meta-analysis showed that transversus abdominis plane blocks significantly reduced postoperative opioid use, 46 quadratus lumborum blocks did not show any significant opioid reduction in a separate RCT.…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…3 But the review article also stressed how donation after cardiac death (DCD) has increased the donor pool for pancreatic transplants. 43…”
Section: Abdominal Transplantmentioning
confidence: 99%
“…1 Weight gain following SPK transplantation, however, is common. 2 Hyperglycaemia may, therefore, also occur due to insulin resistance, or the effect of immunosuppressants such as steroids and calcineurin inhibitors. Recurrent T1D in a transplanted pancreas is rare.…”
Section: Case Progressionmentioning
confidence: 99%